Renewable hydrogen production from the organic fraction of municipal solid waste through a novel carbon-negative process concept. (1st August 2022) - Wang, Shule; Yang, Hanmin; Shi, Ziyi; Zaini, Ilman Nuran; Wen, Yuming; Jiang, Jianchun; Jönsson, Pär Göran; Yang, Weihong
Abstract: Bioenergy with carbon capture and storage (BECCS) is one of the prevailing negative carbon emission technologies. Ensuring a hydrogen economy is essential to achieving the carbon-neutral goal. In this regard, the present study contributed by proposing a carbon negative process for producing high purity hydrogen from the organic fraction of municipal solid waste (OFMSW). This integrated process comprises anaerobic digestion, pyrolysis, catalytic reforming, water-gas shift, and pressure swing adsorption technologies. By focusing on Sweden, the proposed process was developed and evaluated through sensitivity analysis, mass and energy balance calculations, techno-economic assessment, and practical feasibility analysis. By employing the optimum operating conditions from the sensitivity analysis, 72.2 kg H2 and 701.47 kg negative CO2 equivalent emissions were obtained by treating 1 ton of dry OFMSW. To achieve these results, 6621.4 MJ electricity and 325 kg of steam were utilized during this process. Based on this techno-economic assessment of implementing the proposed process in Stockholm, when the negative CO2 equivalent emissions are recognized as income, the internal rate of return and the discounted payback period can be obtained as 26% and 4.3 years, respectively. Otherwise, these values will be 13% and 7.2 years. Highlights: Treat organic fraction of municipal solid waste (OFMSW) for Hydrogen production. Optimum operating condition selected from sensitivity analysis. 72.2 kg H2 and 701.47 kg negative emissions are achieved per ton OFMSW. 25.5 kWh electricity is needed to produce 1 kg of H2 . The process can be profitable in Stockholm with payback in 4.3 years.